Medical internship training during the COVID-19 pandemic - A case of 'sacrificial pawns' or not? - Veena S. Singaram; Kimesh Naidoo; Labby Ramrathan (AOSIS, 2022)
Background: Newly qualified medical practitioners in South Africa (SA) are part of the frontline health care workers who face Africa's most severe coronavirus disease 2019 (COVID-19) pandemic. The experiences of interns during the pandemic reflect SA's preparedness to respond in a crisis and inform strategies that could be adopted to balance training and service in resource-challenged contexts. Aim: To explore the strengths, weaknesses, opportunities and threats posed during the first wave of the COVID-19 pandemic as reflected on by interns within the clinical training platforms in SA. Setting: Public hospitals in KwaZulu-Natal. Methods: An online questionnaire consisting of eight open-ended questions based on the SWOT framework related to personal and professional perspectives to clinical training during the COVID-19 pandemic was developed using SurveyMonkey. All data were collected remotely via social media platforms. Data were thematically analysed. Results: Forty-six interns reflected on personal and systemic challenges as the major threats and weaknesses in intern training during the COVID-19 pandemic. Extrapolating on strengths and opportunities, there were three overarching learnings interns reflected on. These related to being a medical professional, communities of practice and the development and enhancement of clinical and non-clinical competencies. Existing challenges in the environment exacerbated the threats posed by COVID-19 and innovative strategies related to improving support, feedback, broadening the intern curriculum and online training. Conclusion: Although the clinical environment where interns learn and work is often stressful and overpowered by high service burdens, there are unique opportunities to enhance self-directed learning and graduate competencies, even in the midst of the COVID-19 pandemic.